Amâlî (Imla) As Arabic Writing Technique - Dicky Rachmat Pauji (Universitas Padjadjaran, 2017)
Amâlî (Imla) is a methodology used in studying Arabic language and literature that has a very wide scope. Amâlî (Imla) itself can be translated as: to dictate, to add, to fill in and etc. Amâlî (Imla) may also be interpreted further by the following narration: A teacher (ustadz) comes to a place like a mosque, an Islamic school or any learning space in general. In the process of teaching and learning, all that are spoken by the teacher is written down by the students on pieces of paper they had prepared earlier then be compiled into a book which will be preserved. This paper presents a brief summary of Amâlî (Imla) as a methodology which is discussed in many Amâlî (Imla) related literature works written from the beginning of 7th century until the 14th century. The subject Amâlî (Imla) is written in exceedingly diverse manner, unique to each of numerous known authors. This paper also discusses about various meaning of the word Amâlî (Imla) that has been interpreted differently among authors. In addition, the method of separating chapters and other minor distinct writing style that each of various groups of Amâlî (Imla) authors had developed was presented in this work. And lastly, this paper discusses the fact that Amâlî (Imla) related textbook authors were not only originated from the Middle East, but also from regions such as Iran (Huzistan) and Andalusia